Application of the theory of stress in dermatology - Matešić, Krunoslav (2008)
Stress is a multifaceted concept that can be viewed on various levels. It can be analyzed from physiological and pathophysiological hormone secretion levels, through the individual’ s quality of live to the traumatic consequences of natural disasters or those affecting individuals exposed to radical changes to sociopolitical systems or war traumas. Stress refers to burdens that the individual experiences as too big for their potential and too demanding for the usual array of behaviours. The state of stress entails unease, usually accompanied by anger and rage or anxiety and depression. In stress, the person, both emotionally and cognitively, behaves differently. Simply put, he either seeks a quick solution or withdraws. Intensity and duration are important characteristics of stress. In the attempt to clarify the mechanisms of stress, influences on the experience of stress are examined, as are copying methods. Hans Selye began research on stress during the 1930’ s. Viewing stress as a reaction of the organism to different physical and physiological factors, Selye became the founder of the first reactionary model for the study of stress. The second theoretical approach to the study of stress is basically an explanation that stress is determined by the nature of the stressor. This paradigm dates back to the late 1960’ s and is called the stimulus model of stress. At approximately the same time a third, the transactional-cognitive model in the study of stress appears, established by Richard Lazarus. The lecture will discuss the theories of stress in dermatological research and interventions.
Projekt MZOS
ENG